Conflicto y cooperación en las relaciones internacionales - Paz Consuelo Márquez-Padilla (Norteamérica)
Different international relations theories have attempted to explain conflict or cooperation in the international arena, but by underlining one, they have underestimated the other. Here the proposal is to give the same importance to both, to make them better understood. The theory of John Rawls establishes specific principles for justice in the international context that are problematic because of the way he selects them, given that he does not consider all countries equal though he does consider individuals equal within the basic structure of society. The proposal presented here for the international context considers all countries equal and helps us understand why sometimes they cooperate and other times they clash. When they act in accordance with the restrictions of a hypothetical construction to take collective action, they achieve stability and order, their decision's are legitimate, and can be considered just, thus fostering peace and cooperation.